SARS-CoV-2 vaccination in patients with inflammatory bowel disease: A systemic review and meta-analysis. Issue 4 (3rd January 2022) - Sung, Kuan-Yi; Chang, Tien-En; Wang, Yen-Po; Lin, Chun-Chi; Chang, Chung-Yu; Hou, Ming-Chih; Lu, Ching-Liang
Abstract : Background: In the coronavirus disease 2019 (COVID-19) pandemic, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) vaccination has been effective in preventing COVID-19 infections and related mortality. The SARS-CoV-2 vaccination was also recommended by the international society for patients with inflammatory bowel disease (IBD). However, IBD patients were not recruited in prospective randomized clinical vaccine studies. To evaluate the efficacy and safety of SARS-CoV-2 vaccination in IBD patients, we conducted this systemic review and meta-analysis. Methods: We systematically searched PubMed, Medline, and the Cochrane Library for studies published between January 1, 2019, and September 9, 2021. Studies written in English reported the efficacy, seroconversion (anti–SARS-CoV-2 anti-spike (S) antibody titer beyond the threshold) rate, and adverse events after the SARS-CoV-2 vaccination in IBD patients. We extracted the author, date, study design, country, types of SARS-CoV-2 vaccination, number of IBD patients receiving SARS-CoV-2 vaccinations, and study outcomes. Published data from the enrolled studies were pooled to determine effect estimates. The study protocol was registered in PROSPERO (CRD42021264993). Results: We analyzed findings from 27 454 IBD patients who received SARS-CoV-2 vaccinations in 11 studies that met the inclusion criteria. The post–SARS-CoV-2 vaccination COVID-19 infection rate was comparable between the IBD patients and non-IBD patients (odds ratio [OR], 1.28 [95% CI, 0.96–1.71]) and higher in nonvaccinated IBD patients compared with vaccinated IBD patients (OR, 8.63 [95% CI, 5.44–13.37]). The adverse event rate, severe adverse events, and mortality after the SARS-CoV-2 vaccination were 69%, 3%, and 0%, respectively. Conclusion: The SARS-CoV-2 vaccine is effective and tolerated in preventing COVID-19 infections in IBD patients. Over 98% of patients had seroconversion after receiving all doses of the SARS-CoV-2 vaccination, and the influence of biologics on vaccination was limited. The SARS-CoV-2 vaccination is recommended for IBD patients.